4-Formylazetidin-2-one as a useful building block for the formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine - Kale, Ajaykumar S.; Sakle, Prathmesh S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
Stereoselective formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine is described starting from an enantiopure formyl-substituted P-lactam. Grignard reaction of the N-Boc-protected-beta-lactam carbonyl group, followed by further transformations, provides a common intermediate for xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine.
Keywords: azetidin-2-one; beta-lactam; Grignard reaction; Phytosphingosine; Sphingosine

Stereoselective synthesis of 3-alkylidene/alkylazetidin-2-ones from azetidin-2,3-diones - Tiwari, Dharmendra Kumar; Shaikh, Ashif Y.; Pavase, Laxmikant S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2007)
Azetidin-2,3-diones have been used as synthons for the synthesis of C-3 alkylidene/alkylazetidin-2-ones. Some of the 3-alkylazetidin-2-ones are well known for their cholesterol absorption inhibitor activity. A regio and stereoselective Grignard reaction on a keto group followed by dehydration using PPh3/CCl4 reagent is a key step in this synthesis. Hydrogenation of the 3-alkylideneazetidin-2-ones provided stereoselectively cis-3-alkylazetidin-2-ones in very good yields. (c) 2006 Published by Elsevier Ltd.
Keywords: 3-diones; azetidin-2; azetidin-2-ones; beta-lactam; Grignard reaction

Synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an important intermediate for (3S,4R)-Cisapride - Shirode, Nilesh M.; Likhite, Anjali P.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2008)
An efficient synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an useful intermediate for the chiral synthesis of important drug molecule Cisapride and its analogs, from enantiopure 4-formylazetidin-2-one is described. Synthesis of trans as well as cis isomers of 4-amino-3-methoxypiperidine from 4-formylazetidin-2-one is also achieved in good yield. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: 4-aminopiperidine; azetidin-2-ones; Cisapride; Staudinger reaction; stereoselective synthesis

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction

Reactivity of thiophenes, oligothiophenes and benzothiophenes - Rajappa, Srinivasachari; Gumaste, Vikas K. (Advances in Heterocyclic Chemistry, 2013)
This article surveys the literature on the reactivity of thiophenes and benzothiophenes published since the appearance of the third edition of Comprehensive Heterocyclic Chemistry. Two areas that have received maximum attention are: (1) homo- and cross-coupling reactions leading to C C bond formation with high site selectivity and under mild reaction conditions, as well as the regioselective introduction of heteroatom substituents and (2) dithienylethenes and their symmetry-allowed photocyclized isomers, with special reference to the use of this photochromic system as photoswitching units.
Keywords: Benzothiophenes and oligothiophenes; Newer results on the reactivity of thiophenes; Pericyclic reactions; Transition metal-catalyzed bond formation